Coherent magnetic nanoinclusions induce charge localization in half-Heusler alloys leading to high-Tc ferromagnetism and enhanced thermoelectric performance. Issue 18 (12th April 2019) - Lu, R.; Lopez, J. S.; Liu, Y.; Bailey, T. P.; Page, A. A.; Wang, S.; Uher, C.; Poudeu, P. F. P.
Abstract : Coherent incorporation of magnetic nanoinclusions into a heavily doped semiconductor leads to overlapping bound magnetic polarons and a drastic reduction of the effective carrier density. Abstract : Performance improvement traditionally realized through a combination of power factor optimization via electronic doping and lattice thermal conductivity reduction using nanostructuring have reached their optimal limits in many leading thermoelectric materials, making further enhancement in the thermoelectric figure of merit extremely challenging. Here, a novel approach to electronic transport engineering using coherent magnetic nanoinclusions is demonstrated. It was found that the incorporation of coherent magnetic full-Heusler (FH) nanoinclusions (Ti(Ni4/3 Fe2/3 )Sn) into a half-Heusler (HH) matrix (Ti0.25 Zr0.25 Hf0.5 NiSn0.975 Sb0.025 ) with optimal doping level and lattice thermal conductivity leads to high Curie temperature ferromagnetism ( T c ∼ 650 K) along with a large reduction in the effective carrier density within the HH matrix. It is believed that the embedded magnetic FH nanoinclusions interact with the spin of itinerant carriers, leading to charge localization and the formation of overlapping bound magnetic polarons (BMPs). This gives rise to significant enhancements of both carrier mobility and thermopower, which minimizes the reduction in the overall power factor, simultaneously with a large drop in the total thermal conductivity owing to the reduction of the electronic contribution to the thermal conductivity. The implementation of the magnetic nanoinclusions strategy in a variety of state-of-the-art thermoelectric materials could pave the way towards even larger figures of merit.